2016
DOI: 10.1093/cid/ciw249
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Differences in the Use of Direct Acting Antiviral Agents for Hepatitis C Virus

Abstract: There were unexplained differences among HCV population subgroups in the receipt of new DAA treatment. Targeted interventions are needed for black patients and younger women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
4
65
0
Order By: Relevance
“…Similarly, we found people with a history of drug use and those on OST showed a trend towards receiving DAAs, although it was not significant for DAAs+PegIFN/RBV. These findings are consistent with data from the United States on HIV co‐infection and advanced‐stage liver disease but not for drug use . In these studies, as well as in another study from Switzerland, people with a history of substance use were less likely to receive new DAAs .…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we found people with a history of drug use and those on OST showed a trend towards receiving DAAs, although it was not significant for DAAs+PegIFN/RBV. These findings are consistent with data from the United States on HIV co‐infection and advanced‐stage liver disease but not for drug use . In these studies, as well as in another study from Switzerland, people with a history of substance use were less likely to receive new DAAs .…”
Section: Discussionsupporting
confidence: 88%
“…Psychiatric co-morbidity was a rare reason for lack of treatment. We stratified the sample by race to determine the reasons underlying the racial disparity in treatment observed in this as well as previous analysis 15 , Table 3 displays the reasons among African American and whites who did not receive DAA treatment during the study timeframe. Whites had a higher proportion of documented alcohol abuse (22.6% vs. 12.7%) than African American patients (p=0.04).…”
Section: Resultsmentioning
confidence: 97%
“…There is evidence, however, that African American patients receive DAAs less often than white patients. In one study of the veteran population with HCV seeking care in the VA system during the DAA era, Kanwal, et al found that black patients had 22% lower odds [Odds Radio (OR): 0.78; 95% CI: 0.73-0.84] of being treated with DAAs than white patients [22]. This difference persisted after adjustment for socioeconomic status, severity of liver disease, comorbidity and healthcare utilization.…”
Section: Potential Contributors To the Elevated Hcc Risk And Higher Mmentioning
confidence: 99%